PERSEPSI DAN ANTUSIASME WAJIB PAJAK TERHADAP IMPLEMENTASI KEBIJAKAN TAX AMNESTY DI KABUPATEN BOJONEGORO TAHUN 2016 ( Studi Empiris pada Wajib Pajak yang terdaftar di KPP Pratama Bojonegoro ) - Nurul Mazidah; Malu'atul Chofifah; Ravicha Ary Dewanti (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2017)
To extract state revenues from the tax sector, real efforts are needed, one of the policies to consider is the enactment of tax amnesty or tax forgiveness. The purpose of this study is To determine the perception and enthusiasm of taxpayers about the application of Tax Amnesty in 2016 in Bojonegoro regency. Research on the perception and enthusiasm of taxpayers To the implementation of tax amnesty In Bojonegoro district in 2016 this is a qualitative research. The population in this study are all taxpayers of individuals or entities in the Bojonegoro region who have followed the Amnesty Tax at stage one to stage two. The sample selection method is random sampling. The results of this study indicate that taxpayers registered in KPP Pratama Bojonegoro very enthusiastic with the implementation of tax amnesty policy. Nevertheless, public perception regarding Tax amnesty also varies. Various forms of socialization have been done by KPP Pratama Bojonegoro but the direct socialization related to law No. 11 of 2016 is still less intense. Despite its implementation or implementation, this policy has a positive and beneficial impact on the country but this policy also has a negative side.